INTEGRASI NILAI-NILAI PENDIDIKAN SOSIAL-BUDAYA DALAM PENDIDIKAN BAHASA INDONESIA - Rama Wijaya Abdul Rozak; Cik Suabuana; Maulia D. Kembara; M.R. Fajar Islamy (Jurnal Semantik, 2021)
Students are required to master and be able to develop a number of competencies to compete in theworld of work. Developing competencies is a must in today's 21st century. In addition, students mustbe able to think at a higher level or often called HOTS (Higher Order Thinking Skills). The problemthat often arises is that it is too focused on developing competencies so that it ignores the socioculturalvalues that apply in society. This study aims to integrate socio-cultural values in PendidikanBahasa Indonesia (PBI) lectures. This is based on the need for students to be smart in verbal andwritten communication and to know the socio-cultural values in order to be able to place themselvesin society. The method used is document analysis in the form of RPS and material from courses andanalyzing the core values of socio-cultural education. The results showed that there were contrastingdifferences between the value of education in PBI and the value of socio-cultural education. However,there is a gap to integrate socio-cultural values into PBI learning, namely by means of explicit andimplicit explanations. Thus, studies in PBI learning do not focus on language provisions, but haveinsight into socio-cultural values.